E-Government Implementation in Public Service Organizations of Developing Economies - Hussen, Kassahun Hassen (Journal of Public Policy and Administration, 2017)
Purpose: The purpose of this research is to implement and test an E-government solution as an intervention mechanism to the challenges of good governance practices in Ethiopian public service organizations. E-government has the ability to transform relationships of public sector organizations with employees, customers and other important stakeholders. It serves a variety of different ends for public sector organizations such as better deliver of service to customers, improving organizational governance to enhance transparency and accountability, improving organizational communication and interaction with stakeholders, empowering employees and management through providing access to organizational information. Hence, E-government has become important component for public sector organizations in enhancing transparency and accountability. Knowledge on E-government has been presented in known outlets, however there is no sufficient research done to see how it can bring behavioral changes specifically enhancing transparency and accountability in the context of developing economies. Methodology: We followed action research methodology to implement the E-government system and qualitative data has been collected through interview, focus group discussion, and workshop for the purpose of diagnosing the challenges of good governance and for evaluating the E-government system. The five-staged action research methodology proposed by Baskerville (1999) has been followed as intervention mechanism in the organizations and further improve the system based on results of E government system evaluation. Results: The evaluation and learning stages showed that the implemented E-government system at the selected three public service organizations has improved the situation. Organizational effectiveness, internal transparency and accountability, collaboration and public participation were improved significantly in those bureaus as a result of the E-government system implemented. Conclusions: We conclude that transparency and accountability on the selected public sector organization were very much improved because of the implemented E-government system. As this project has addressed accountability and responsibility at least to some extent, other organizations that are the same situation and in the same context can benefit from it. The implemented E-government system introduced can offer better results if the first version can be enhanced to a fully-fledged system provided that all the necessary resources such as manpower, financial, and material resources are in place.